2021
DOI: 10.3233/jad-210003
|View full text |Cite
|
Sign up to set email alerts
|

Verbal Fluency in Mild Alzheimer’s Disease: Transcranial Direct Current Stimulation over the Dorsolateral Prefrontal Cortex

Abstract: Background: Recent studies showed that in healthy controls and in aphasic patients, inhibitory trains of repetitive transcranial magnetic stimulation (rTMS) over the right prefrontal cortex can improve phonemic fluency performance, while anodal transcranial direct current stimulation (tDCS) over the left prefrontal cortex can improve performance in naming and semantic fluency tasks. Objective: This study aimed at investigating the effects of cathodal tDCS over the left or the right dorsolateral prefrontal cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 101 publications
0
3
1
Order By: Relevance
“…These were not directly stimulated by left inferior atDCS. However, results of previous studies also show a significant effect of atDCS over the left IFG on semantic WF performance in healthy elderly participants ( Meinzer et al, 2013 ; 2015 ) and in patients with dementia-related cognitive decline ( Penolazzi et al, 2013 ; Smirni et al, 2021 ), but their experimental task procedure and the associated word retrieval of the subjects were very different and not very comparable to our tasks.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…These were not directly stimulated by left inferior atDCS. However, results of previous studies also show a significant effect of atDCS over the left IFG on semantic WF performance in healthy elderly participants ( Meinzer et al, 2013 ; 2015 ) and in patients with dementia-related cognitive decline ( Penolazzi et al, 2013 ; Smirni et al, 2021 ), but their experimental task procedure and the associated word retrieval of the subjects were very different and not very comparable to our tasks.…”
Section: Discussioncontrasting
confidence: 74%
“…It is possible that stimulation of the temporal cortex could lead to better outcomes in MCI, as also suggested by Chen et al (2022) . Moreover, cathodal stimulation of the right DLPFC improved WF in mildly affected AD patients by supporting left hemisphere networks through short-term inhibition ( Smirni et al, 2021 ). From this, one could assume that the same stimulation conditions do not apply to MCI patients and healthy elderly and therefore do not lead to comparable results.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that tDCS may improve global cognition [12,14,56,57], recognition memory [12], verbal fluency [14,16], executive function [14], and depression [15] in patients with AD. Interestingly, a single session of tDCS in the area of the left DLPFC in AD patients demonstrated enhanced recognition memory [12].…”
Section: Transcranial Direct Current Stimulationmentioning
confidence: 99%
“…Numerous studies have explored the effects of tDCS on verbal fluency, with particular focus on the left IFG [ 50 ], right IFG [ 51 ], left dlPFC [ 52 ], and right dlPFC [ 53 ]. Among the main candidate regions, the left IFG, commonly known as Broca’s area, has been extensively investigated for its involvement in response selection, representing the verbal component of verbal fluency.…”
Section: Introductionmentioning
confidence: 99%